A comprehensive review on phytochemistry, pharmacology, and flavonoid biosynthesis of Scutellaria baicalensis - Zi-Long Wang; Shuang Wang; Yi Kuang; Zhi-Min Hu; Xue Qiao; Min Ye (Pharmaceutical Biology, 2018)
Context: Scutellaria baicalensis Georgi (Lamiaceae) is a popular medicinal plant. Its roots are used as the famous traditional Chinese medicine Huang-Qin, which is recorded in Chinese Pharmacopoeia, European Pharmacopoeia, and British Pharmacopoeia. Objective: This review comprehensively summarizes research progress in phytochemistry, pharmacology, and flavonoid biosynthesis of S. baicalensis. Methods: English and Chinese literature from 1973 to March 2018 was collected from databases including Web of Science, SciFinder, PubMed, Elsevier, Baidu Scholar (Chinese), and CNKI (Chinese). Scutellaria baicalensis, chemical constituents, phytochemistry, biological activities, and biosynthesis were used as the key words. Results: A total of 126 small molecules (1–126) and 6 polysaccharides have been isolated from S. baicalensis. The small molecules can be classified into four structural types, namely, free flavonoids, flavonoid glycosides, phenylethanoid glycosides, and other small molecules. Extracts of S. baicalensis and its major chemical constituents have been reported to possess anti-viral, anti-tumor, anti-bacterial, antioxidant, anti-inflammatory, hepatoprotective, and neuroprotective activities. Key steps in the biosynthetic pathways of Scutellaria flavonoids have also been summarized. Conclusions: This article could be helpful for researchers who are interested in the chemical constituents, bioactivities, biosynthesis, and clinical applications of S. baicalensis.